Power control and simulation of a building integrated stand-alone hybrid PV-wind-battery system in Kasuga City, Japan - Ayas Shaqour; Hooman Farzaneh; Yuichiro Yoshida; Tatsuya Hinokuma (Energy Reports, 2020)
With buildings accounting for high electrical demand and GHG emissions in Japan, enabling higher penetration of hybrid renewable energy systems can significantly reduce their load demand. This paper proposes an efficient power control scheme and design for a hybrid renewable standalone system installed on the roof of a building in Kasuga-City, Japan. The proposed system consists of three PV modules with a total power of (480 W), a wind turbine (400 W), a lead-acid battery (30 Ah), an inverter, and controllers. The main purpose of this research is to implement a well-defined control scheme for standalone Hybrid Renewable Energy Systems (HRES), that has a low level of complexity in terms of Maximum Power Point Tracking (MPPT) with a limited number of components in order to reduce costs and provide high power quality output. The main control layers of the model include the Perturb and Observe (P&O) controller used for MPPT of both the wind turbine and PV systems and a PI controller used to control both the battery charging and inverter of the system. The proposed control scheme also includes two charging modes for the battery when there is no load; Bulk mode for faster charging and Float mode for slower charging to keep the battery fully charged, as its charge decrease with time Dynamic modeling and simulation are accomplished using MATLAB-SimulinkTM 9.3, to evaluate the performance and system's dynamics, considering two scenarios of (1) variable weather conditions and (2) different charging modes of battery. The results of the simulation reveal that the proposed system can utilize an efficient battery charging control configuration, eliminating the need for a specific battery converter, providing high output power quality with the Total Harmonic Distortion(THD) below 1% in steady-state, and sustaining output voltage magnitude and frequency under changing system dynamics.
Keywords: 330; Battery control; Buck converter; Building-integrated renewables; Hybrid renewables; Inverter control; MATLAB; Maximum power tracking; P&O; PI control; PV; Simulink; Solar array; Standalone; Wind turbine